Reflecting on the PRET A Rapporter Framework Via a Field Study of Adolescents’ Perceptions of Technology and Exercise - Edwards, Helen; McDonald, Sharon; Zhao, Tingting; Humphries, Lynne (Human Technology, 2013)
PRET A Rapporter (PRETAR) was developed to explicitly structure user-centered evaluation studies to ensure all necessary elements are individually and independently considered. Its creators see its benefit as twofold: for study design and in retrospective evaluations. We evaluate PRETAR’s potential by applying it retrospectively to one of our eHealth field studies in which we investigated the design requirements for mobile technologies that would support and motivate adolescents to exercise opportunistically. We also use PRETAR to evaluate the key literature for this eHealth study. This shows that typically the research methodology is under-reported. Then we document the study in terms of its purpose, resources, ethical concerns, data collection and analysis techniques, and manner of reporting the study. Finally, our reflection on the use of PRETAR leads us to propose that four different modes of the framework should be applied during the course of a study, that is, when reviewing, planning, conducting, and discussing.